Synthesis and Characterization of Mn-Zn Ferrite Nanomaterials by Chemical Co-Precipitation Method - Srivastava, Ravi Prakash (My University, 2008)
Mn-Zn ferrite is a soft magnetic material and is widely used in electronic applications. In order to utilise these materials for the application at higher frequencies it is essential that particle size should be small. Further for the better properties of these materials the particles should be uniform and non-agglomerated. In order to achieve these properties many research groups have shifted towards developing these materials at the nanoscale as the performance in their ceramic preparation route is reaching their limits due to their higher electrical conductivity and domain wall resonance. Therefore the synthesis has been done with the help of chemical co-precipitation method so that we can get high purity material with a small particle size. The main focus of the present work is to synthesize the Mn-Zn ferrite from pure chemicals as well as from the waste material (blue dust) which is the natural ore of the iron. The characterization of the materials synthesized from pure chemicals and blue dust has been done with the help of X-ray analysis, EDS, SEM, TEM and DTA techniques. The results shows that the material synthesized from the blue dust has nearly same properties as that from the pure chemicals. Hence in the coming future the synthesis of Mn-Zn ferrite material from the waste material (blue dust) can be helpful in the cost minimization and we can get cheap electonic devices.
M.Tech. (Materials Science and Engineering)
Keywords: Mn -Zn ferrites, co precipitation